The social life of nanotechnology - Harthorn, Barbara Herr, 1951-; Mohr, John. (New York : Routledge, 2012)
'This volume shows how nanotechnology takes on a wide range of socio-historically specific meanings in the context of globalization, across multiple localities, institutions and collaborations, through diverse industries, research labs, and government agencies and in a variety of discussions within the public sphere itself. It explores the early origins of nanotechnologies; the social, economic, and political organization of the field; and the cultural and subjective meanings ascribed to nanotechnologies in social settings.'--
Includes bibliographical references and index.
Keywords: Nanotechnology -- Social aspects